2019
DOI: 10.3390/ma12030446
|View full text |Cite
|
Sign up to set email alerts
|

Scanning 3DXRD Measurement of Grain Growth, Stress, and Formation of Cu6Sn5 around a Tin Whisker during Heat Treatment

Abstract: The 3D microstructure around a tin whisker, and its evolution during heat treatment were studied using scanning 3DXRD. The shape of each grain in the sample was reconstructed using a filtered-back-projection algorithm. The local lattice parameters and grain orientations could then be refined, using forward modelling of the diffraction data, with a spatial resolution of 250 nm. It was found that the tin coating had a texture where grains were oriented such that their c-axes were predominantly parallel to the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 43 publications
(53 reference statements)
0
37
0
Order By: Relevance
“…A robust, although time-consuming, technique for the local measurement of intra-granular strains in the bulk at micrometre spatial and 10 −4 strain accuracy is Differential Aperture X-ray Microscopy (DAXM) (Larson et al, 2002;Levine et al, 2006;Robach et al, 2013;Tardif et al, 2016) [32,33,34,35], a variant of polychromatic X-ray Laue micro-diffraction. More recently, using monochromatic micro-beam scanning, a far-field detector and an established 3DXRD indexing procedure (ImageD11) (Wright, 2017) [36], Hektor et al has shown local sensitivity of the method to hydrostatic strain (Hektor et al, 2019) [37], and Hayashi et al has demonstrated mapping the full strain tensor over a region containing 37 3 voxels at 1.2 µm spacing deep inside a steel specimen (Hayashi et al, 2019) [38]. Simons et al, 2018) [39,40,41].…”
Section: Intragranular Strain (Type III Stresses)mentioning
confidence: 99%
See 1 more Smart Citation
“…A robust, although time-consuming, technique for the local measurement of intra-granular strains in the bulk at micrometre spatial and 10 −4 strain accuracy is Differential Aperture X-ray Microscopy (DAXM) (Larson et al, 2002;Levine et al, 2006;Robach et al, 2013;Tardif et al, 2016) [32,33,34,35], a variant of polychromatic X-ray Laue micro-diffraction. More recently, using monochromatic micro-beam scanning, a far-field detector and an established 3DXRD indexing procedure (ImageD11) (Wright, 2017) [36], Hektor et al has shown local sensitivity of the method to hydrostatic strain (Hektor et al, 2019) [37], and Hayashi et al has demonstrated mapping the full strain tensor over a region containing 37 3 voxels at 1.2 µm spacing deep inside a steel specimen (Hayashi et al, 2019) [38]. Simons et al, 2018) [39,40,41].…”
Section: Intragranular Strain (Type III Stresses)mentioning
confidence: 99%
“…In the monochromatic scanning method in (Hektor et al, 2019) [37] and (Hayashi et al, 2019) [38], the 2D deformation reconstruction problem is circumvented and reduced to an indexing problem. The local strain values represent a weighted mean of the total volume contributing to the indexed reflections for one voxel.…”
Section: Acquisition Modes and Spatial Sensitivity In Mapping Local Dmentioning
confidence: 99%
“…This tool has been used with success in the past (cf. Hektor et al, 2019;Henningsson et al, 2020) and can provide an understanding of the limitations and benefits of scanning 3DXRD reconstruction methods. Briefly, the simulation input is specified as a set of cubic single-crystal voxels featuring individual strains and orientations together with an experimental setup.…”
Section: Validationmentioning
confidence: 99%
“…Initially, Hayashi et al (2015Hayashi et al ( , 2017 proposed a method for a per-voxel strain refinement to approximate intragranular strains using scanning 3DXRD data. Unfortunately, this procedure was shown to introduce bias in the reconstruction related to strain state (Hayashi et al, 2019;Hektor et al, 2019). These obstacles were later overcome by Henningsson et al (2020), who proposed an inversion method that takes the tomographic nature of the problem into account.…”
Section: Introductionmentioning
confidence: 99%
“…Point scanning techniques using a focused X-ray beam such as DAXM [27] have been the most capable technique to perform elastic strains mapping [28] but remain limited to small volume close to the specimen surface. More recently, the scanning 3DXRD modality, first introduced by Hayashi [29], allowed to characterize local strains at sub-micrometre length scales [30,31]. The method was further refined by Hektor et al [32] using forward simulation to improve its sensitivity.…”
Section: Introductionmentioning
confidence: 99%